ANALISIS PENGGUNAAN METODE ALTMAN, SPRINGATE, DAN ZMIJEWSKI DALAM MEMPREDIKSI KEBANGKRUTAN PERUSAHAAN PERTAMBANGAN BATUBARA PERIODE 2012-2014 - WIWIT FIRMA MEITA, ELVINNA (Jurnal Akuntansi AKUNESA, 2015)
Abstract Coal company performance degradation due to slowing economic growth in China and declining selling prices. The negative impact of the economic slowdown in China is decreasing export value of Indonesian coal for China's new policies that restrict imports of coal. Coal decreasing selling prices as a result of oversupply and overcapacity in the market. Excess supply in the Chinese market, create demand for coal in China decreased. Problems like the above if the ongoing impact on the possibility of the company went bankrupt, which means the failure of the company running the company's operations to generate profits. Bankruptcy prediction is needed as an early warning before making investment decisions in a company. This study uses descriptive qualitative approach with the objective to analyze how prdiksi bankruptcy coal mining company listed in the Indonesia Stock Exchange in 2012-2014 using the Altman Z-score, Springate and Zmijewski. Z-scores of comparison three models Altman Z-Score, Springate models and models over the years 2012-2014 Zmijewski above can be seen that the Altman Z-Score models and models of bankruptcy prediction Springate provide a level equal to the value of a percentage of 88.888%. However, different deenganZmijewski usage models that give a percentage of the value of the bankruptcy of 66.666%. Key words: bankrupt, early warning , Altman Z-score, Springate,Zmijewski